Foundations of Buddhism - Dhakal, Dev Raj (Research Nepal Journal of Development Studies, 2021)
Buddha was born in Nepal. The crown prince after turning or being Buddha gave the Buddhists philosophy to the world. The three characteristics of existence that have in mind are the characteristics of impermanence (Anitya), suffering (Duhkha), and not-self (Anatma). These three characteristics are always present in or are connected with existence, and they tell us about the nature of existence. The main objective of the study is to analyze specifically the basic foundation of Buddhism in Nepal. The study is predominantly a review paper. It has reviewed the prominent research articles available in Nepal. Finally, the study concludes as morality is simply good conduct. It is the specific analysis of the eight-fold path. The Noble Eightfold Path has been traditionally divided into the three groups of training or the three ways of practice and they are morality or good conduct (Shila), meditation or mental development (Samadhi), and wisdom or insight (Prajna). The Noble Eightfold Path is the means of arriving at the goal of Buddhism.